A corpus-based analysis of stance markers in upper and lower proficiency level argumentative essays by Saudi learners - Afzaal, Muhammad; El-Dakhs, Dina Abdel Salam; Mardini, Nahlah; Ambreen, Fatima; Ismail, Hala (Frontiers in Education, 2025)
Strategic use of stance-taking devices in English language academic texts is a key indicator of the proficiency of any academic writer. While this is true of first language (L1) and second language (L2, ESL or EFL) writers alike, developing the ability to express authorial stance is far more challenging for the non-native writers who may lack the L1 cultural exposure to understand and express stance accurately in L2 writing. The present corpus-based study was designed to identify frequency and patterns of stance-taking devices in the writing of lower-proficiency (novice) and upper-intermediate Saudi EFL writers in comparison with native writers. The study found that lower-proficiency (novice) writers tended to use evidential verbs similar to native writers, with the use of stance markers varying considerably in the lower-proficiency (novice) and upper-intermediate writers’ texts. Self-mention was overused by the lower-proficiency (novice) writers, whereas the upper-intermediate writers overused modal hedges in comparison with lower-proficiency (novice) and native writers. The lower-proficiency (novice) writers used approximate hedges to a greater extent. Unlike native speakers who used contrastive markers frequently, the lower-proficiency (novice) and upper-intermediate writers used these markers to a similar extent.